Possible Rapid Therapeutics for SARS Coronavirus 2 RNA-dependent RNA polymerase: A Systematic Review: Possible Rapid Therapeutics for SARS Coronavirus 2 … - Asghariazar, Vahid; Mazloum Jalali, Kamyar; Aghebati-Maleki, Ali; Biparva Haghighi, Somayeh; Balar, Negin; Peeri-Dogaheh, Hadi; Karami, Chiman (Iranian Journal of Pharmaceutical Sciences, 2022)
Research confirms that viral polymerases play a key role in viral genome replication and transcription. Hence, they are essential for the multiplication and survival of viral particles. Our review is limited to original papers in the English language from 2019 to 2020 using various databases, including PubMed, Scopus, Google Scholar, and Science direct. Out of 159 papers, 27 drugs may effectively prevent RNA-dependent RNA polymerase (RdRP), of COVID-19, agreed in order of drug discovery years and paper publication, respectively. In this paper, we realized that the structure comparison and sequence alignment suggest that the mode of substrate RdRP is highly conserved in diverse RNA viruses, providing a foundation for designing broad-spectrum antiviral drugs based on nucleotide analogs.